THE IMPACTS OF PRE-ECLAMPSIA IN THE GESTATIONAL PERIOD - Rodrigues Fernandes, Daniele; Silva Oliveira, Geane; Rolim de Oliveira, Rafaela; Caroline de Souza, Anne (Health and Society, 2023)
Pregnancy is considered an event that is part of a woman’s development, it is at this stage where several changes occur, involving everything from the physical to the emotional state. Pregnancy is also accompanied by risks involving the mother or fetus in constant formation, leading her to face several challenges, especially in the presence of pathologies and comorbidities. Hypertensive disease during pregnancy, pre-eclampsia, is a complication that occurs after the twentieth week of pregnancy, affecting a large part of the population and presenting high mortality rates. Analyze the impacts of pre-eclampsia during pregnancy. The present integrative review of the literature, which occurred based on the guiding question “what are the complications of pre-eclampsia during the gestational period?”, where articles were selected according to the criteria: inclusion and exclusion, articles contained in the databases : Scientific Electronic Library Online (SciELO) and LILACS using the descriptors: “pregnancy”; “pre-eclampsia” and “complications”, duly registered in the Health Sciences Descriptors (DeCS) and associated with the Boolean operator and. Given the findings, it was possible to highlight studies on the main complications related to pre-eclampsia during the gestational period. The research included a total sample of 10 articles for discussion, among which it was possible to see that the main impacts of pre-eclampsia are related to maternal and feral death, the possibility of prematurity, low weight, growth retardation and other factors related to the development. In this way, it was possible to analyze the articles and respond to the central objective of the research, considering that it brought relevant data on the topic, highlighting the impacts of pre-eclampsia, associated complications, diagnosis, treatment, monitoring and main risks. Furthermore, the research also aims to encourage more and more new research so that it can contribute to a greater body of knowledge in the area.